2016
DOI: 10.1002/ca.22690
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal immaturity, rostral sparing, and disparate hip morphologies as biomechanical causes for Legg‐Calvé‐Perthes' disease

Abstract: Legg-Calvé-Perthes' (Perthes') disease is a developmental disease of the hip joint that may result in numerous short and long term problems. The etiology of the disease remains largely unknown, but the mechanism is believed to be vascular and/or biomechanical in nature. There are several anatomical characteristics that tend to be prevalent in children with Perthes' disease, namely: skeletal immaturity, reduced height, and rostral sparing. We present an overview of the literature, summarizing the current unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 177 publications
(237 reference statements)
0
12
1
Order By: Relevance
“…During childhood, the femoral head is supplied exclusively by the medial circumflex artery (Berthaume et al, ). In the first stage of LCPD, blood flow to the medial circumflex artery is restricted (Berthaume et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During childhood, the femoral head is supplied exclusively by the medial circumflex artery (Berthaume et al, ). In the first stage of LCPD, blood flow to the medial circumflex artery is restricted (Berthaume et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…During childhood, the femoral head is supplied exclusively by the medial circumflex artery (Berthaume et al, ). In the first stage of LCPD, blood flow to the medial circumflex artery is restricted (Berthaume et al, ). Although the precise aetiology of the ischemia is unknown (Alpaslan, Aksoy, & Yazici, ), such restriction can be caused by extension of the hip (e.g., standing), which stretches the medial circumflex artery over the tendon of the external obturator (Lauritzen, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously proposed five mechanisms for the pathology of Perthes’ disease, 15 and the implications for the morphology of the juvenile hip and the biomechanics of the hip joint. 16 From these we suggested that fracture and collapse of the femoral head, even in an immature epiphysis, is unlikely.…”
Section: Introductionmentioning
confidence: 99%